Contribution of Arbuscular Mycorrhizal Fungi, Phosphate–Solubilizing Bacteria, and Silicon to P Uptake by Plant - Etesami, Hassan; Jeong, Byoung Ryong; Glick, Bernard R. (Frontiers in Plant Science, 2021)
Phosphorus (P) availability is usually low in soils around the globe. Most soils have a deficiency of available P, if they are not fertilized; they will not be able to satisfy the phosphorus requirement of plants and as a result, limit agricultural production. Phosphorus fertilization is generally recommended to manage phosphorus deficit; however, the low efficiency of the available phosphorus fertilizer use in acidic and in calcareous soils restricts the phosphorus availability, and phosphorus fertilizers are also a cause of significant environmental concerns. Use of arbuscular mycorrhizal fungi (AMF), phosphate–solubilizing bacteria (PSB), and silicon (Si) is a greatly effective and economical way to improve the availability and use efficiency of phosphorus in its deficit. In this review paper, we showed contribution of Si, PSB, and AMF in improving the phosphorus availability and as a result, its uptake by plants. Based on what is known about them, the combined strategy of using silicon along with AMF and PSB may be highly useful in improving the phosphorus availability and as a result, its uptake by plants compared to using either of them alone. Better understanding how the two microorganism groups and silicon interact is crucial in preserving soil fertility and improving the economic and environmental sustainability of crop production. This review paper summarizes and discusses the current knowledge concerning the interactions among AMF, PSB, and Si in enhancing P availability and its uptake by plant in sustainable agriculture, and attempts to outline promising directions for future research.